PROMOTING READING CONFERENCE AS AN EFFECTIVE TECHNIQUE IN TEACHING READING OF EFL LEARNERS - Khoiriyah Khoiriyah (Universitas PGRI Madiun, 2014)
This study examines the effectiveness of reading conference technique in teaching reading of EFL learners. Thirty two learners consisting of 12 males and 20 females from the second grade of English Department at Nusantara PGRI Kediri University were participated in the study. To conduct the study, pre-test were administered before applying treatment, while post-test were administered after applying treatment. Quantitative method and pre-experimental approach were applied in this present study and t- test was used to analyze the data. The analyses resulted in the finding that the score of post-test exhibited significantly better than the score of pre-test. Thus, it can be said that reading conference is effective in teaching reading at the second grade learners of English Department at Nusantara PGRI Kediri University.